Gonococcal Conjunctivitis in Adults: Case Report and Retrospective Review of Cases in Alberta, Canada, 2000–2016. Issue 1 (January 2019) - Belga, Sara; Gratrix, Jennifer; Smyczek, Petra; Bertholet, Lindsay; Read, Ron; Roelofs, Kelsey; Singh, Ameeta E.
Abstract : Background: A case of gonococcal conjunctivitis (GC) prompted us to review the reported cases and treatment regimens of GC in Alberta, Canada. Methods: Gonococcal cases reported from 2000 to 2016 were extracted from the provincial sexually transmitted infection reporting database. The diagnosis of GC was based on a positive culture and/or nucleic acid amplification test from the eye. Results: A total of 45 cases of GC were reported in adults. Three quarters (75.6%; n = 34) of the cases were diagnosed using culture, 57.8% (n = 26) of cases were among men, and 55.5% (n = 25) were diagnosed since 2014. Very few (13.3%; n = 6) of the cases were treated according to current Canadian Guidelines on Sexually Transmitted Infections, using 2 g of ceftriaxone in combination with azithromycin or doxycycline. Results of test of cures were available for 15.6% (n = 7) of the cases and occurred within 10 to 79 days (median = 26 days) after treatment; all were negative. Conclusions: Gonococcal conjunctivitis was relatively uncommon in our region, but given its potential for severe manifestations and sequelae coupled with the rising rates of gonorrhea; it remains important to consider this diagnosis in sexually active individuals presenting with purulent conjunctivitis. Additional studies are needed to inform treatment recommendations and to evaluate outcomes of infection. Abstract : Over the course of 16 years, 45 cases of gonococcal conjunctivitis were reported in adults. Very few cases were treated according to guidelines.